Effects of an exogenous ketone ester using multi-omics in skeletal muscle of aging C57BL/6J male mice - Roberts, Brandon M.; Deemer, Sarah E.; Smith, Daniel L.; Mobley, James A.; Musi, Nicolas; Plaisance, Eric P. (Frontiers in Nutrition, 2022)
Exogenous ketone ester supplementation increases circulating ketone concentrations without the challenges imposed by ketogenic diets. Our group has shown that oral R,S-1,3, butanediol diacetoacetate (BD-AcAc2) consumption causes body weight loss with increases in circulating ketones. We have previously shown a diet consisting of 25% BD-AcAc2 can maintain lean body mass (LBM) and induce fat mass (FM) loss, but the underlying mechanisms are still unknown. Therefore, the purpose of this study was to determine if a diet consisting of 25% BD-AcAc2 (ketone ester, KE) would alter body composition, transcriptional regulation, the proteome, and the lipidome of skeletal muscle in aged mice. We hypothesized that the KE group would remain weight stable with improvements in body composition compared to controls, resulting in a healthy aging phenotype. Male C57BL/6J mice (n = 16) were purchased from Jackson Laboratories at 72 weeks of age. After one week of acclimation, mice were weighed and randomly assigned to one of two groups (n = 8 per group): control (CON) or KE . A significant group by time interaction was observed for body weight (P<0.001), with KE fed mice weighing significantly less than CON. Fat mass increased over time in the control group, but was unchanged in the KE group. Furthermore, lean mass was not different between CON and KE mice despite KE mice weighing less than CON mice. Transcriptional analysis of skeletal muscle identified six genes that were significantly higher and twenty genes that were significantly lower in the KE group compared to CON. Lipidomic analysis of skeletal muscle identified no differences between groups for any lipid species, except for fatty acyl chains in triacylglycerol which was 46% lower in the KE group. Proteomics analysis identified 44 proteins that were different between groups, of which 11 were lower and 33 were higher in the KE group compared to CON. In conclusion, 72-week old male mice consuming the exogenous KE, BD-AcAc2, had lower age-related gains in body weight and FM compared to CON mice. Furthermore, transcriptional and proteomics data suggest a signature in skeletal muscle of KE-treated mice consistent with markers of improved skeletal muscle health.